(untitled) (Kronika Bydgoska, 2012)
Bydgoszcz in the Second Republic of Poland was the most important rowing centre in Poland. It was here that the best Polish regatta course was located, and many strong clubs operated. Owing to the popularity of rowing in the city, collective efforts were madę to prepare Bydgoszcz rowers for the Olympic Games in Amsterdam in 1928. A group of competitors, members of the Bydgoszcz Rowing Association was selected, and German coach Goetz was employed. After a series of ąualification competitions, a four with coxswain turned out to be the best in Poland and gained the right to participate in the Olympic Games. In Amsterdam, on the Slotem course, the team: Edmund Jankowski, Franciszek Bronikowski, Leon Birkholc, Bernard Ormanowski and coxswain Bolesław Drewek won the bronze medal. When the rowers returned to Bydgoszcz, they were officially welcomed at the railway station and escorted to the club’s seat on the Brda River by thousands of residents. Due to different life fortunes of the five rowers, they never again started in one team.